Overall survival of patients with KIT-mutant metastatic GIST in the era of multiple kinase inhibitor availability - Valerie Haller; Carina Reiff; Rainer Hamacher; Karina Kostbade; Moritz Kaths; Juergen Treckmann; Stefanie Bertram; Yasmin Zaun; Sebastian Bauer; Johanna Falkenhorst (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose The prognosis of patients with metastatic GIST and imatinib-sensitive primary mutations has significantly improved. However, limited data are available to inform patients about outcomes across different lines of treatment. This retrospective analysis aims to evaluate patient outcomes at a large German GIST referral center over the past 15 years. Patients and methods Overall survival (OS) and progression-free survival (PFS) were analyzed in patients with metastatic GIST, with diagnosis of metastases between 2008 and 2021, when at least three lines of treatment were available in Germany (n = 174). Results The median overall survival far exceeds historical data for patients with primary exon 11 and exon 9 mutations (median OS in palliative treatment with imatinib: 7.1 years; median OS in second-line palliative treatment with sunitinib: 2.9 years; median OS in third-line palliative treatment with regorafenib: 1.9 years). Among those patients who received palliative imatinib treatment, no significant difference in median OS survival was observed between those who had received perioperative imatinib for localized disease and those who did not. Furthermore, the location of metastases significantly impacted survival, whereas the time between the initial diagnosis and the diagnosis of metastases had no significant effect on survival. Conclusion In conclusion, this study provides a novel, real-world reference for survival outcomes in patients with metastatic GIST.